BPA and its analogs increase oxidative stress levels in in vitro cultured granulosa cells by altering anti-oxidant enzymes expression. (5th April 2022) - Sabry, R.; Nguyen, M.; Younes, S.; Favetta, L.A.
Abstract: Bisphenol A is a widespread endocrine disruptor with numerous effects on reproductive functions. Limitations on BPA in manufacturing has prompted the use of analogs, such as BPS and BPF, with limited research on their safety. The objective of this study was to evaluate the effects of BPA and its analogs on oxidative stress levels within bovine granulosa cells and to measure the expression of key antioxidant genes. Results indicate that BPA and BPF reduce cell viability and induce mitochondrial dysfunction and all three bisphenols increased production of reactive oxygen species as early as 12hrs post exposure. BPA increased the levels of antioxidants at 12hrs at the mRNA and protein levels, while these results were not significant at 48hrs. These results together suggest that BPA and its analogs can induce oxidative stress within bovine granulosa cells, although not necessarily through common mechanisms. Therefore, the use of BPA analogs may have to be re-considered. Highlights: BPA/BPS/BPF reduce viability & induce oxidative stress in bovine granulosa cells. These bisphenols increase antioxidant expression after acute exposure. BPA analogs have similar effects to BPA, yet may work through different mechanisms.